ACDPN Proposes Roadmap for Access to Prevention Services for Black English-speaking Families - African Canadian Development and Prevention Network (2013)

African-Canadian Career Excellence : Undergraduate Survey 2011-2012 Summary Report - Community Economic Development and Employability Corporation (CEDEC) (2013)
This summary report provides the final data analysis and interpretation of the 2011-2012 undergraduate student survey on perceptions of transition to employment in Montreal. As one step in the African-Canadian Career Excellence (ACCE) initiative aimed at countering the migration of Black graduates from Montreal, this summary will inform the design of development training for young graduates to facilitate their career launch and advancement in Quebec. Information and insights herein were provided by the following members of ACCE: Dorothy W. Williams of the Black Community Resource Centre (BCRC), Dwight Best of the African and Caribbean Students’ Network of Canada (ACSioN), Tamara Hart of the Tyndale St-Georges Community Centre, Velda Bourne, Karima West, and Nina Kim and Larissa Milo-Dale of the Community Economic Development and Employability Corporation (CEDEC). Preliminary data analysis and interpretation were contributed by Jan Warnke J W COMM INC.

Initiative pour l'excellence de la carrière des Afro-Canadiens : Sondage réalisé auprès des étudiants du premier cycle universitaire - Community Economic Development and Employability Corporation (CEDEC) (2013)
Ce rapport sommaire consigne les résultats et l'interprétation de l'analyse des données du sondage réalisé auprès des étudiants au premier cycle universitaire de 2011-2012 sur leurs perceptions de la transition vers le marché du travail de Montréal. Comme l’une des démarches de l'Initiative pour l’Excellence de la carrière des Afro-Canadiens consiste à contrer la migration des diplômés noirs de Montréal, ce rapport influencera l'élaboration de formations de perfectionnement pour les jeunes diplômés afin de faciliter l’amorce de leur carrière et leur progression professionnelle au Québec.